2021
DOI: 10.3389/fmars.2021.687738
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Analysis of Juvenile White Sharks Inside a Nursery Area Reveals Foraging in Demersal-Inshore Habitats and Trophic Overlap With Sympatric Sharks

Abstract: Knowledge about top predators’ trophic ecology is crucial for defining their role in ecosystems, understanding habitat preferences, characterizing life stage-specific feeding habits, and evaluating their interaction with fisheries. In the northeastern Pacific, white sharks (Carcharodon carcharias) occupy coastal habitats during the early life stages, including Bahía Sebastián Vizcaíno (BSV) in Mexico, which is a known nursery area. Although BSV presumably provides high prey abundance, the trophic ecology of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…millennia and persists even during El Niño/La Niña Events (Thunell and Kepple, 2004;Yang et al, 2017). In addition, examination of C and N isotope ratios of young sharks sampled off central Baja California did not show marked differences between (Garcıá-Rodrıǵuez et al, 2021. Multiple studies over time have shown the GC's food web to be enriched in 13 C and 15 N relative to the Pacific (e.g.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…millennia and persists even during El Niño/La Niña Events (Thunell and Kepple, 2004;Yang et al, 2017). In addition, examination of C and N isotope ratios of young sharks sampled off central Baja California did not show marked differences between (Garcıá-Rodrıǵuez et al, 2021. Multiple studies over time have shown the GC's food web to be enriched in 13 C and 15 N relative to the Pacific (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Hussey et al, (2010) reported trophic discrimination factors for vertebral tissues of 1.5 and 3.8 ‰ for carbon and nitrogen, respectively, based on semi-controlled feeding experiments on large sharks. Off central Baja California, small White Sharks (200 cm TL) feed mostly on demersal fishes, with a limited contribution of pelagic fishes (Tamburin et al, 2020, Garcıá-Rodrıǵuez et al, 2021. However, the largest shark caught in the Pacific and those caught in the GC should feed on marine mammals based on their size and known ontogenetic diet shifts (Tricas and McCosker, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations